Trusting Former Rebels: An Experimental Approach to Understanding Reintegration after Civil War - Michal Bauer; Nathan Fiala; Ian Levely (Institute for the Study of Labor (IZA), 2014)
The stability of many post-conflict societies rests on the successful reintegration of former soldiers. We examine social capital of former soldiers in Northern Uganda, where the Lord's Resistance Army forcibly recruited tens of thousands of youth during a recent brutal conflict. We use a set of interlocked experiments to study behavior of ex-soldiers jointly with the behavior of receiving communities towards this group. Consistent with theories that highlight the importance of cooperation during war, we find that individual cooperativeness robustly increases with the length of time a person was with the LRA, especially among those who were abducted during early age. Furthermore, parents of former-soldiers are aware of the behavioral difference: they trust ex-soldiers more because they expect them to be more trustworthy. Last, we find no evidence of preference-based discrimination, suggesting that anger is attenuated when communities do not attribute responsibility for committed violence to returning soldiers. Together, the results reveal that the impact of child soldiering on social capital, in contrast to human capital, is not necessarily detrimental and, speculatively, may facilitate reintegration.
Keywords: C93; D03; D74; O12; 330; trust; cooperation; civil war; endogenous preferences; soldiers; reintegration